Provisional Crown Dislodgement during Scuba Diving: A Case of Barotrauma - Meenal Nitin Gulve; Nitin Dilip Gulve (Case Reports in Dentistry)
Changes in ambient pressure, for example, during flying, diving, or hyperbaric oxygen therapy, can lead to barotrauma. Although it may seem that this issue was neglected in dental education and research in recent decades, familiarity with and understanding of these facts may be of importance for dental practitioners. We report the case of a patient who experienced barotrauma involving dislodgement of a provisional crown during scuba diving. Patients who are exposed to pressure changes as a part of their jobs or hobbies and their dentists should know the causes of barotrauma. In addition, the clinician must be aware of the possible influence of pressure changes on the retention of dental components.